Cooperative and competitive learning as transformative factors of educational processes for extracurricular skill enhancement - Cavaletto, Giulia Maria; Miglietta, Anna (Frontiers in Education, 2024)
The learning process goes beyond the acquisition of curricular cognitive elements to include extracurricular skills. This extended concept has attracted renewed attention through the European Council Recommendation (2018) on skills development for lifelong learning in schools. The Organization for Economic Cooperation and Development has also highlighted the relevance of socio-emotional skills for learning and life chances.The official uptake of extracurricular skills in curricula poses schools and educators the challenge of finding ways to conceptualise, teach, and assess them. To this end, co-operative learning and peerto-peer education hold a prominent place among educational strategies alternative to conventional teaching practises. Both actively engage students and have a positive impact on achievement in curricular disciplines and on the development of lifelong learning skills and social and emotional competences.The present study presents a case study in which collaborative learning was supported via a digital platform. We analysed the qualitative data collected in Italian schools taking part in the Kids4alll, a Horizon 2020 project. The project's aim is to improve lifelong learning skills directly and other skills indirectly through collaborative learning based on the "buddy method" (pairs or groups of peers working together).Our findings reveal the potential benefit of peer-to-peer approaches. This potential extends to the development of co-operative skills used in school context and transferable to other areas, along with the acquisition of character-building skills. However, a criticality in the application of peer learning interventions is that many teachers are often ill prepared to implement cooperative learning in classroom practice or lack sufficient training in matching peer-to-peer work and pedagogical needs.